Isu - isu sosial - Hamidah Ab. Rahman author; Nor Akmar Nordin author; Fadilah Zaini author; Azizah Rajab author; Durrishah Idrus author; Norashikin Mahmud author; Husain Mahmood author; Ishak Mad Shah author; Azlah Md. Ali author; Thuaibah @ Suaibah Abu Bakar author; Rozeyta Omar author; Nurul Shaza Sharum author; et al. (Skudai : Penerbit Universiti Teknologi Malaysia, 2008)
Includes bibliographical references